Transformasi Pola Pikir Peserta Didik melalui Pembelajaran Pendidikan Agama Islam di Sekolah Menengah Pertama - Fahmi, Hanan Ari; Utomo, Tri Prasetyo (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2023)
Educational institutions that have structured objectives and implementation are quality institutions. The influence held by educational institutions will later equip them to build and change mindsets. The problem for educational institutions today is how to change the mindset of students to be of higher quality. This study aims to reveal the systematics and implementation of educational institutions in transforming the mindset of students. The method used in this study is a qualitative method by applying data collection through observation, interviews, and relevant documentation. The results showed the transformation of the mindset of students through several stages. The first was to design learning so that students experienced a change in mindset through practice or experience. The second is the implementation of transformation through learning. The last stage was an evaluation of learning and the transformation of students' mindsets.